Strategies for Overcoming Cinderella Complex Syndrome in Adolescent Girls - miranti, miranti; Diah Karmiyati, Diah Karmiyati (SM Institute, 2024)
The Cinderella Complex syndrome is a phenomenon that affects adolescent girls in contemporary society. This study aims to explore strategies to overcome this syndrome through psychoeducation. The research method used is a qualitative approach with thematic analysis. Data were collected through interviews and observations of female millennial students. The results show that factors such as 1) having a boyfriend, 2) receiving male attention, 3) depending on and being influenced by others, 4) lack of confidence in their abilities, 5) desire to marry young, 6) having fears that can inhibit success, 7) lack of independence, 8) received parenting styles influence the Cinderella Complex syndrome in adolescent girls. The implications of this research are the need for psychological interventions, such as psychoeducation, to help adolescent girls overcome their fear of independence and develop self-confidence. Hopefully, these findings will contribute to understanding and addressing the Cinderella Complex syndrome in adolescent girls in contemporary society